2012
DOI: 10.1161/circinterventions.112.968792
|View full text |Cite
|
Sign up to set email alerts
|

Should We Recommend Oral Anticoagulation Therapy in Patients With Atrial Fibrillation Undergoing Coronary Artery Stenting With a High HAS-BLED Bleeding Risk Score?

Abstract: Background— Recent European guidelines for the management of atrial fibrillation recommend oral anticoagulation (OAC) in patients with CHA 2 DS 2 -VASc score (congestive heart failure, hypertension, age ≥75 years, diabetes, history of previous stroke, vascular disease, age 65–74 years, and sex category [female]) ≥1. The HAS-BLED score (Hypertension, Abnormal renal/liver function, Stroke, Bleeding history or predisposition, Labil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 25 publications
2
39
2
Order By: Relevance
“…Therefore, DAPT was preferred over a single antiplatelet agent, likely because 73% of patients had an ACS as index event, in accordance with other studies. 24, 39 In agreement with our results, both Tomita et al 43 and Okumura et al 44 recently reported that patients with AF and modified CHA2DS2-VASc score=1 (registry did not include peripheral artery disease or aortic plaque) had a truly low risk of thromboembolism (0.86%), even when female sex was excluded (1.0%), suggesting that the use of anticoagulation must be avoided in this subgroup of patients. 43, 44 On the other hand, Abe et al 45 found no significant sex difference in the annual incidence of thromboembolism (1.2% for women, 1.6% for men; odds ratio 0.72, 95% CI 0.28-1.62; P=0.44).…”
Section: Study Limitationssupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, DAPT was preferred over a single antiplatelet agent, likely because 73% of patients had an ACS as index event, in accordance with other studies. 24, 39 In agreement with our results, both Tomita et al 43 and Okumura et al 44 recently reported that patients with AF and modified CHA2DS2-VASc score=1 (registry did not include peripheral artery disease or aortic plaque) had a truly low risk of thromboembolism (0.86%), even when female sex was excluded (1.0%), suggesting that the use of anticoagulation must be avoided in this subgroup of patients. 43, 44 On the other hand, Abe et al 45 found no significant sex difference in the annual incidence of thromboembolism (1.2% for women, 1.6% for men; odds ratio 0.72, 95% CI 0.28-1.62; P=0.44).…”
Section: Study Limitationssupporting
confidence: 91%
“…In agreement with other authors, we also found a strong correlation between stroke and bleeding risk scores, with patients with CHA2D2S-VASc ≥2 being those with the highest bleeding risk, defined as HAS-BLED ≥3. 39 In contrast, we found no association between CHA2D2S-VASc score and MACE or MAE. Therefore, decisions concerning the optimal antithrombotic management of patients with AF undergoing DAPT might be a safe strategy after coronary stenting in patients with AF and low thromboembolic risk.…”
Section: Consequences Of Tt On Mortality and Other Adverse Events In contrasting
confidence: 77%
“…Our data thus extend the available evidence base of the CHA 2 DS 2 -VASc method in predicting stroke, TE, or both in patients with AF, and show that the CHA 2 DS 2 -VASc score enables the identification of a larger number of AF patients for whom oral anticoagulation would be recommended. 24 Our meta-analysis also reveals a powerful predictive value of both the CHADS 2 and CHA 2 DS 2 -VASc for the highest-risk stratum of patients, independent of anticoagulation. Our results indicate that cardiovascular events might also occur in anticoagulated AF patients and reveal a stepwise increase in stroke or TE events upon increasing scores across risk strata in anticoagulated patients.…”
Section: Discussionmentioning
confidence: 52%
“…In another study, anticoagulated (with VKAs) AF-patient who needed PCI-SI were grouped according to their bleeding risk which was assessed by the HAS-BLED score [75]. More than 70% of patients had a score of 3 or higher.…”
Section: Can Triple Therapy Be Individualized In Af-patients?mentioning
confidence: 99%